Three-Dimensional Analytical Modeling of Rotational Eddy Current Speed Sensor - Mirzaei M.; Ripka P. (IEEE Sensors Council, 2024)
—The main goal of this paper is to present a novel 3D analytical method for precise and fast modeling of rotational eddy current speed sensors with cylindrical structures. An equivalent linearized model is developed using a multi-slice structure. The cylindrical structure of rotational eddy current sensors is modeled using the multi-slice linearized structure. The 3D distribution of induced eddy current in the rotating conductive rods is considered in the analytical modeling. The method of separation of variables using Fourier series is utilized for the analytical analysis of rotational eddy current speed sensors. The new calculation method is tested on the eddy current speed sensor with perpendicular coils and different rotating rods. The analytical results are compared with the calculations of 3D time harmonic and time stepping finite element methods. The measurements on the sensor prototype verified the calculations. When compared to the 3D Time Harmonic FEM, the 3D analytical method is 12-times faster.
Keywords: 3D analytical method; Fourier series; eddy current analysis; measurement; rotational speed sensor